1993
DOI: 10.1128/iai.61.4.1500-1508.1993
|View full text |Cite
|
Sign up to set email alerts
|

Filamentous growth and elevated vaginopathic potential of a nongerminative variant of Candida albicans expressing low virulence in systemic infection

Abstract: The vaginopathic potential and the intravaginal morphology of a nongerminative variant of Candida albicans, strain CA-2, were studied in a rat vaginitis model. Although it expressed low virulence in systemic infections, strain CA-2 was capable of causing a vaginal infection of the same duration and extent as that obtained in rats challenged with the germ-tube-forming strain C. albicans 3153 from the stock collection or with a fresh clinical isolate of C. albicans from a case of human vaginitis. During the expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
36
0

Year Published

1993
1993
2010
2010

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(43 citation statements)
references
References 28 publications
7
36
0
Order By: Relevance
“…In the self-healing mucosal model of infection (De Bernardis et al, 1993), the overall kinetics of fungus clearance from rat vagina was quite similar with all mutants and wild-type strain. However, the early rate of clearance (day 0-7 interval) was significantly (P < 0.05, Student's t-test, two-tailed) more accelerated when the challenger was the homozygous strain.…”
Section: Camp65 Mutants Have Markedly Decreased Experimental Pathogenmentioning
confidence: 73%
See 1 more Smart Citation
“…In the self-healing mucosal model of infection (De Bernardis et al, 1993), the overall kinetics of fungus clearance from rat vagina was quite similar with all mutants and wild-type strain. However, the early rate of clearance (day 0-7 interval) was significantly (P < 0.05, Student's t-test, two-tailed) more accelerated when the challenger was the homozygous strain.…”
Section: Camp65 Mutants Have Markedly Decreased Experimental Pathogenmentioning
confidence: 73%
“…However, this null mutant was also significantly less pathogenic in a model of mucosal infection, an observation that has never been reported with other hyphae-defective mutants. The observation that CAMP65 gene plays also a role in mucosal virulence is relevant because the virulence traits which allow mucosal or deep-seated invasion may not be the same, and different are also the mechanisms of host response against the two infections (De Bernardis et al, 1993).…”
Section: Fig 5 Experimental Pathogenicity Of Camp65 Mutants In Mousmentioning
confidence: 99%
“…Vaginal fluid was taken from each animal every 2 days with a calibrated (1-l) plastic loop (Dispoinoc; PBI). The contents of each loop were vigorously suspended in 0.1 ml of PBS and aliquots were streaked over SDA plates containing 0.05% (wt/vol) chloramphenicol and incubated at 28ЊC for 48 to 72 h. One vaginal sample per rat per culture was evaluated, and the rat was considered infected when at least 1 CFU was present in one loop of vaginal fluid, i.e., a count of Ն10 3 CFU/ml (6,7). At intervals during the vaginal infection, the colonies developed on SDA were reidentified by standard diagnostic criteria (4,7).…”
Section: Methodsmentioning
confidence: 99%
“…Using oophorectomized, estrogen-treated rats, we obtained circumstantial evidence about the role of aspartyl-proteinase(s), a putative virulence factor of C. albicans in the pathogenesis of the vaginal infection (4,7). We have also recently demonstrated that the vaginal environment has unique, though still undefined, properties allowing for antigenic variations and hypha formation even by nongerminative mutants of C. albicans (6,9). Finally, we have shown that anti-idiotypic antibodies are elicited to a substantial level in the vaginas of rats immunized intravaginally or subcutaneously with an anti-yeast killer toxin monoclonal antibody.…”
mentioning
confidence: 99%
“…[47][48][49][50] It has been shown in animal models of mucosal and systemic infections that the germ tube formation is an important feature in the virulence of C. albicans. 51,52 The compounds (PhSe) 2 and (MeOPhSe) 2 abolished the germ tube formation. These compounds are efficient in inhibiting both Candida growth and germ tube formation, which indicates their great potential as an antifungal agent.…”
Section: Discussionmentioning
confidence: 97%